Differential Susceptibility of Mycoplasma and Ureaplasma Species to Compound-Enhanced Copper Toxicity - Totten, Arthur H.; Crawford, Cameron L.; Dalecki, Alex G.; Xiao, Li; Wolschendorf, Frank; Atkinson, Thomas P. (Frontiers in Microbiology, 2019)
Rationale: Mycoplasmas represent important etiologic agents of many human diseases. Due to increasing antimicrobial resistance and slow rate of novel discovery, unconventional methods of drug discovery are necessary. Copper ions are utilized in host microbial killing, and bacteria must regulate intracellular Cu concentrations to avoid toxicity. We hypothesized that human mollicutes may have susceptibility to Cu-induced toxicity, and compounds that augment copper-dependent killing. Methods: Mycoplasma pneumoniae (Mpn), Ureaplasma parvum (Up), Ureaplasma urealyticum (Uu) and Mycoplasma hominis (Mh) were exposed to CuSO4 to determine minimal inhibitory concentrations (MICs). Once inhibitory concentrations had been determined, bacteria were treated with an FDA-approved drug disulfiram (DSF), glyoxal bis(4-methyl-3-thiosemicarbazone) (GTSM) and 2,9-dimethyl-1,10-phenanthroline (neocuproine), with or without Cu2+, to determine compound MICs. Results: Ureaplasma species and Mh were able to tolerate 30-60 µM CuSO4, while Mpn tolerated over 10-fold higher concentrations ( >1 mM). GTSM inhibited growth of all four organisms, but was unaffected by Cu2+ addition. Inhibition by GTSM was reduced by addition of the cell-impermeant Cu chelator, bathocuproine disulfonate. Neocuproine exhibited Cu-dependent growth inhibition of all organisms. DSF exhibited Cu-dependent growth inhibition against Mh at low micromolar concentrations, and at intermediate concentrations for Mpn. Conclusions: MICs for CuSO4 differ widely among human mollicutes, with higher MICs for Mpn compared to Mh, Uu and Up. DSF and Neocuproine exhibit Cu-dependent inhibition of mollicutes with copper concentrations between 25-50 µM. GTSM has copper-dependent anti-microbial activity at low levels of copper. Drug enhanced copper toxicity is a promising avenue for novel therapeutic development research with Mycoplasma and Ureaplasma species.